Roll drive mechanism with planetary gearbox for cold pilger pipe rolling mills - Danchenko , V.M.; Dobrov , I.V.; Semichev , A.V. (Theory and Practice of Metallurgy, 2025)
Purpose. Creation and study of a roll drive mechanism with a planetary gearbox, which will ensure a reduction in axial forces in the production of thin-walled pipes and it will expand the range of pipes obtained on cold pilger rolling mills. Methodology. The work includes research on determining the parameters of the roll drive of cold pilger rolling mills using the graph-analytical method of studying the kinematics of mechanisms. Results. The roll drive mechanism with a planetary gearbox will ensure regulation of the angular speed of rotation of the rolls and a reduction in axial forces. Scientific novelty. The influence of the geometric parameters of the roll drive on the value of the angular speed of the rolls, which ensure a reduction in axial forces, has been determined. Practical significance. The roll drive mechanism with a planetary gearbox allows obtaining high-quality thin-walled pipes with the possibility of expanding the range.